2020
DOI: 10.3390/jcm9041146
|View full text |Cite
|
Sign up to set email alerts
|

Sympatho–Vagal Dysfunction in Patients with End-Stage Lung Disease Awaiting Lung Transplantation

Abstract: Although the literature demonstrates that cardiac autonomic control (CAC) might be impaired in patients with chronic pulmonary diseases, the interplay between CAC and disease severity in end-stage lung disease has not been studied yet. We investigated the effects of end-stage lung disease on CAC through the analysis of heart rate variability (HRV) among patients awaiting lung transplantation. Forty-nine patients on the waiting list for lung transplantation (LTx; 19 men, age 38 ± 15 years) and 49 healthy non-sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Moreover, a recent study in pulmonary patients awaiting transplantation, reported that patients with more severe lung disease showed an autonomic profile characterized by a prevalent cardiac vagal respiratory modulation and a loss of sympathetic efference compared to less severe lung disease patients. 4 In support, Volterrani et al also reported an increase in vagal activity (as indicated by an increased high-frequency HRV power) in non-hypoxemic or in mildly hypoxemic COPD patients, which was suggested to be associated with reduced FEV 1 and an increased bronchoconstriction. 31 In that study, patients were also less able to respond to sympathetic and parasympathetic stimuli, compared with the healthy subjects, which is in line with our findings in IPF.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, a recent study in pulmonary patients awaiting transplantation, reported that patients with more severe lung disease showed an autonomic profile characterized by a prevalent cardiac vagal respiratory modulation and a loss of sympathetic efference compared to less severe lung disease patients. 4 In support, Volterrani et al also reported an increase in vagal activity (as indicated by an increased high-frequency HRV power) in non-hypoxemic or in mildly hypoxemic COPD patients, which was suggested to be associated with reduced FEV 1 and an increased bronchoconstriction. 31 In that study, patients were also less able to respond to sympathetic and parasympathetic stimuli, compared with the healthy subjects, which is in line with our findings in IPF.…”
Section: Discussionmentioning
confidence: 88%
“…Tobaldini et al reported autonomic dysregulation in patients with end-stage lung disease awaiting transplantation. 4 In patients with chronic obstructive pulmonary disease (COPD), although diurnal variation in heart rate variability (HRV) was normal, impairments in HRV during a stimulus have been reported. 5,6 Long-term oxygen therapy seems to improve the HRV dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that double lung transplant recipients could have compatible responses with complete cardiac denervation (i.e., compared to heart–lung transplanted) [ 6 ]. Besides, after double lung transplant, patients had an abnormal heart rate and blood pressure responses during autonomic tests (e.g., Valsalva manoeuvre and adenosine administration) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was widely documented in current literature that breathing is a powerful modulator of heart rate variability (HRV) [ 4 ]. HRV analysis has proven to be a reliable, non-invasive method to investigate the autonomic neural modulation of cardiovascular functions, and a decline of HRV has shown to be related to higher cardiovascular risk and poor prognosis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the application of HRV in other settings such as pulmonary diseases revealed interesting novel data. In fact, in comparison to healthy subjects, patients with end-stage lung diseases awaiting lung transplantation showed a predominant sympathetic modulation and lower markers of vagal modulation, but the more severe the disease, the lower the sympathetic control [ 8 ].…”
mentioning
confidence: 99%